Executing Race : Early American Women's Narratives of Race, Society, and the Law - Harris, Sharon M. (Book collections on Project MUSE., 2005)
At the 2005 meeting of the Society of Early Americanists, Annette Kolodny called for more literary-historical scholarship that speaks to the hard facts of women's lives in the colonial Americas, scholarship more alert to the human costs for Euro-American, African American, and Native American women of transatlantic imperialism and the local cultural regimes that sustained it. Sharon Harris's Executing Race: Early American Women's Narratives of Race, Society, and the Law advances this important project. As readers of Legacy know, Sharon Harris has made many significant contributions to the study of early American women's writing. Her Selected Writings of Judith Sargent Murray (Oxford University Press, 1995) reintroduced the incomparable early American feminist to literary scholarship; Harris also edited the well-received anthology American Women Writers to 1800 (Oxford University Press, 1996), which recovered almost one hundred woman-authored texts representing women's ideas and experiences in the colonial and early national eras. Executing Race is most notable for its new and revealing biographies of lesser-known early American women authors such as Lucy Terry and Ann Eliza Bleecker, along with its clear-sighted assessment of how Anglophone North American white women both profited from and lost by colonialism.